((2x)/5)-((4x+3)/2)=1

Simple and best practice solution for ((2x)/5)-((4x+3)/2)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((2x)/5)-((4x+3)/2)=1 equation:


x in (-oo:+oo)

(2*x)/5-((4*x+3)/2) = 1 // - 1

(2*x)/5-((4*x+3)/2)-1 = 0

(-1*(4*x+3))/2+(2*x)/5-1 = 0

(-1*5*(4*x+3))/(2*5)+(2*2*x)/(2*5)+(-1*2*5)/(2*5) = 0

2*2*x-1*5*(4*x+3)-1*2*5 = 0

-16*x-15-10 = 0

-16*x-25 = 0

(-16*x-25)/(2*5) = 0

(-16*x-25)/(2*5) = 0 // * 2*5

-16*x-25 = 0

-16*x-25 = 0 // + 25

-16*x = 25 // : -16

x = 25/(-16)

x = -25/16

x = -25/16

See similar equations:

| ((2x)/5)-((4x+9)/6)=2 | | ((4x)/2)+((3x+9)/6)=2 | | 11x-99=-11 | | 2x/5=(4/4)-(4x+6)/2 | | ((3x-1)/6)-((x+3)/4)=(7/12) | | 6x^2+17x+7/3x+4 | | 2x/5=(-4x+6)/2 | | 33-4x=5x+20 | | ((3x-1)/6)-((x+3)/4)=7/12 | | 1234567890qwertyuiop+9876543210asdfghjkl-1357924680zxcvbnm= | | x*x+2x+9=0 | | 29-x/4=x+5 | | 2x+14=45 | | 11=2x+y | | 5x-10=3x+3 | | -3m^2-27m=0 | | x=4x+312 | | x=14x+12 | | -132-16x+x^2=0 | | 3x*7=20x+10 | | 3x*7=10x+10 | | 2m-12=4(2+3m) | | 3x*7=210 | | a^2x^2-10ax+16=0 | | 3x^2+4xy+3y^2=1 | | 67-3x=6x+19 | | 3x^2+3x=58 | | 3(4y+3)=2(3y+5) | | logy=2.7 | | -2x-4(x-2y)=14 | | 80=50 | | 2x+3x^2=55 |

Equations solver categories